2005
DOI: 10.1007/s00227-005-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying effects of pollution on biodiversity: a case study of highly diverse molluscan assemblages in the Mediterranean

Abstract: Structured sampling designs are important in the assessment of environmental impacts of variable ecological systems. Recent developments have provided a useful framework extending existing univariate techniques into a multivariate context. Measures of taxonomic relatedness have also been introduced, which complement existing measures of diversity of assemblages. In this study, the potential effects of sewage discharge on spatial patterns of highly diverse molluscan assemblages in a Mediterranean rocky subtidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 76 publications
2
46
1
5
Order By: Relevance
“…Indices of taxonomic distinctness have previously been found to be more sensitive to human disturbance than other diversity indices (Warwick & Clarke 1995, Terlizzi et al 2005, Roberts & Connell 2008, but this was not supported in our study. Although none of the indices tested using 1-way ANOVAs discriminated significant differences between control and impacted groups, the behaviour of taxonomic distinctness indices in response to enrichment by sewage suggests that they are in fact less sensitive than conventional indices.…”
Section: Taxonomic Distinctness Versus Other Diversity Indicescontrasting
confidence: 99%
See 2 more Smart Citations
“…Indices of taxonomic distinctness have previously been found to be more sensitive to human disturbance than other diversity indices (Warwick & Clarke 1995, Terlizzi et al 2005, Roberts & Connell 2008, but this was not supported in our study. Although none of the indices tested using 1-way ANOVAs discriminated significant differences between control and impacted groups, the behaviour of taxonomic distinctness indices in response to enrichment by sewage suggests that they are in fact less sensitive than conventional indices.…”
Section: Taxonomic Distinctness Versus Other Diversity Indicescontrasting
confidence: 99%
“…They found that phylogenetic diversity was sensitive to the experimental manipulation of both factors, whereas Shannon diversity was not. In the same way, Terlizzi et al (2005) found significant differences in AvTD values between control and impact locations for subtidal mollusc communities around a sewage outfall, but no significant difference in the mean number of species. Nevertheless, in other habitats (freshwater streams), taxonomic distinctness measures have been found unsuitable for detecting disturbance.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Polyplacophora, like most gastropod species, seem to prefer non-polluted habitats. Earlier studies (Airoldi, 2003;Terlizzi et al, 2005a) have advanced the possible explanation that the increase of suspended solids near the sewage discharges could change the sedimentation rates, which may have negative effects on gastropods. Atalah & Crowe (2012) have also found consistent differences in the assemblages of molluscs related with nutrient enrichment, which suggests that those assemblages can be potential indicators of pollution in coastal areas.…”
Section: Sublittoral Fringementioning
confidence: 99%
“…Nevertheless there are several studies focusing on intertidal populations of polychaetes (Dauer & Conner, 1980;Elías et al, 2006;Jaubet et al, 2011), molluscs (Bishop et al, 2002;Terlizzi et al, 2005a;Vallarino and Elías, 2006;Atalah & Crowe, 2012) or crustaceans (Calcagno et al, 1998;De-la-Ossa-Carretero et al, 2010). But studies dealing with the effect on the entire intertidal benthic community are very rare (Littler & Murray, 1975;López-Gappa et al, 1990;Archambault et al, 2001, Klein & Zhai, 2002.…”
Section: Introductionmentioning
confidence: 99%